2011
DOI: 10.1227/neu.0b013e318222dc4c
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Ultrasonography for Diagnosis of Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage: Mean Blood Flow Velocity Ratio of the Ipsilateral and Contralateral Middle Cerebral Arteries

Abstract: In patients with SAH, the I/C mBFV demonstrated a more significant correlation to vasospasm than the absolute mean flow velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Seventeen studies (n = 2870 patients) met inclusion criteria. 3,13,15,16,22,27,29,30,33,34,[39][40][41]44,46,47,51 Study characteristics are summarized in Table 1. No studies addressed the comparative impact of TCD vasospasm on functional outcome and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies (n = 2870 patients) met inclusion criteria. 3,13,15,16,22,27,29,30,33,34,[39][40][41]44,46,47,51 Study characteristics are summarized in Table 1. No studies addressed the comparative impact of TCD vasospasm on functional outcome and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…However, this may not represent a clinically significant deficit, as multiple studies have now demonstrated that using the Lindegaard ratio is less predictive than using absolute velocity values in identifying angiographic vasospasm [12,13]. In addition, using the absolute flow velocity values of the MCA alone appears to allow diagnosis of angiographic vasospasm with high sensitivity and specificity [1416]. The Presto system also has the added benefit of simultaneous bilateral monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The Lindegaard ratio (LR) between the middle cerebral artery and external carotid artery velocities can help differentiate between vasospasm and hyperemia. LR values greater than 3 have been accurate in differentiating clinical and radiographic vasospasm from hyperemia [69, 70] (see Table 2). However, this data cannot be used in isolation as not all vasospasm leads to ischemic injury, and a significant proportion of ischemic injury can occur with (normal) TCD velocities <120 cm/s [71].…”
Section: Cerebral Blood Flowmentioning
confidence: 99%